Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Intégrer la dimension de genre dans le développement de clusters - Département du commerce, des investissements et de l'innovation; Organisation des Nations Unies pour le développement industriel (ONUDI, 2019)
Keywords: EDI; OFDIG; afrique; approches et analyses; asie; autodétermination; discipline; entrepreneuriat; genre; identités LGBTQIA2+; international; rapports sociaux de sexe; régions géographiques; sciences de la gestion; thématiques; économie; égalité des sexes

Paid–unpaid work continuum of women: Home-based workers and self-employed women in the national capital region - Sengupta, Sudeshna (Indian Journal of Labour Economics, 2019)
Women’s work is a continuum that intersperses productive work with reproductive work, unpaid work with paid work and all kinds of activities with leisure and self-care. She plans, manages and implements her work at home, often being responsible for all the three domains. Women from working-class families may seem to be making a “choice” in deciding the continuum, and delving deep, we find that it is more often a “coping mechanism” in “managing poverty” of all forms—income, time and opportunity. This paper explores how women’s organisation of work is influenced by the interplay of three institutions—State, market and family, and how gendered division of work is reproduced in the process. © 2019, Indian Society of Labour Economics.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; division sexuelle du travail; famille; inde; pauvreté; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail de reproduction; travail gratuit; travail rémunéré; travailleuses à domicile

Ethnocentrisme occidental et perceptions du harem - Ahmed, Leila (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2010)
En 1980, lors de la conférence de la National Women’s Studies Association qui s’est tenue à Bloomington, Indiana, j’ai assisté à une présentation sur « Les femmes dans l’islam » au cours de laquelle je suis intervenue vivement, depuis ma place dans le public, car les intervenantes invitées, trois femmes arabes, présentaient, selon moi un tableau idéalisé de la situation des femmes dans l’islam. Les sociétés islamiques se distinguaient peut-être même plutôt – c’est en tout cas ce que je pensais à l’époque – par le fait qu’elles plaçaient sans équivoque les femmes sous le contrôle des hommes et par le fait qu’elles accordaient aux hommes, de façon tout aussi explicite, le droit à une sexualité et le droit d’exploiter les femmes. Comme le soutenaient les intervenantes, à son avènement l’islam avait apporté un certain nombre de progrès positifs pour les femmes en Arabie. Il avait également accordé certains droits aux femmes tels que le droit à la propriété (qui, en Occident, ne fut accordé aux femmes qu’au dix-neuvième siècle et qui n’est d’ailleurs toujours pas accordé aux femmes selon, parexemple, la loi rabbinique, tout comme le droit de témoigner). Et on ne pouvait certainement pas dire que l’islam était plus malveillant à l’égard des femmes que les deux autres religions monothéistes. Cependant, il me semblait que cela ne justifiait en rien le fait de minimiser la position d’approbation flagrante qui est celle de l’islam en ce qui concerne la supériorité des hommes et le contrôle exercé par ces derniers sur les femmes. Ni d’ailleurs le fait d’occulter les difficultés rencontrées par les femmes, en particulier en ce qui concerne les lois sur le mariage, le divorce et la garde des enfants. Cet article est la traduction de : « Western Ethocentrism and Perceptions of the Harem », Feminist Studies, vol. 8, n°3, autumn 1985, p. 521-534. Cet article a été écrit en 1982 donc avant la disparition de l’Union Soviétique qui date de 1992.
Keywords: approches et analyses; asie; cours; discipline; droits des femmes*; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; occident; orient; premier cycle; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sciences juridiques; sciences sociales; sociologie; stéréotypes; thématiques; voiles islamiques

Being "Good" or Being "Popular": Gender and Ethnic Identity Negotiations of Chinese Immigrant Adolescents - Baolian Qin, Desiree (Journal of Adolescent Research, 2009)
Keywords: 2000 à aujourd'hui; 2000-2009; adolescence; amériques; approches et analyses; asie; chine; corps; cours; discipline; identité des femmes*; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexualité; thématiques; travail; états-unis

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Femmes, ethnicité et religion : la communauté tamoule hindoue du Sri Lanka à Montréal - St-Germain Lefebvre, Catherine (Université du Québec à Montréal, 2008)
Convaincue que les femmes, de par leur rôle dans les rapports sociaux de sexe, ont un rôle important à jouer dans la transmission de l'identité ethnique aux jeunes générations, nous avons voulu, dans ce mémoire, mettre à jour ce phénomène tel qu'il se déploie dans la communauté tamoule du Sri Lanka immigrée à Montréal. La perspective féministe en influence la trame de fond, contribuant à orienter le choix du sujet ainsi que son traitement. Ce mémoire est le fruit d'une recherche exploratoire de type qualitatif. Il repose sur un terrain de recherche mené au temple hindou Thiru Murugan situé à Dollard-des-Ormeaux, municipalité de l'ouest de l'île de Montréal. Il a pour objectif de définir la contribution spécifique de femmes de cette communauté à la « production de l'ethnicité » tamoule, au sens entendu par la sociologue des relations ethniques, Danielle Juteau. Ce mémoire s'appuie sur un cadre théorique contribuant à jeter les bases d'une définition sociologique de l'ethnicité, où non seulement le rôle des femmes dans sa production/reproduction est mise de l'avant, mais où se dégage également l'importance de la composante religieuse dans l'affirmation ethnique, particulièrement en contexte migratoire. Cette recherche analyse d'une part la perception du rôle des femmes dans les rapports de sexe tels qu'ils se déploient dans la communauté tamoule montréalaise et telle qu'elle a été exprimée par les personnes interrogées dans le cadre de cette étude. Il s'attarde d'autre part à l'implication des femmes de cette communauté dans la transmission de la langue, de la religion et de la culture. Ce mémoire démontre que les idéaux associés à la conception de la féminité influencent à· maints égards le rôle des femmes dans les rapports sociaux de sexe à l'oeuvre dans la communauté étudiée. Ce rôle amène celles-ci à s'impliquer activement dans la transmission de leur identité ethnique auprès des générations nées au Québec. De plus, la pratique religieuse jouant un rôle important dans la formation identitaire de nos répondant(e)s, la dimension religieuse est omniprésente dans le bagage ethnique transmis par les femmes aux jeunes générations. Par leur travail actif et conscient lié à la transmission de la langue, de la culture et de la religion aux jeunes de la communauté, ces femmes participent activement à reproduire les frontières ethniques de leur communauté et contribuent, par cela, à la « production de l'ethnicité » tamoule hindoue du Sri Lanka en contexte québécois. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Femmes, Ethnicité, Religion, Transmission, Hindouisme, Tamoul, Sri Lanka.
Keywords: IREF; amériques; approches et analyses; asie; discipline; femmes* tamoules; hindouisme; montréal; mémoires/thèses; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sri lanka

South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe